Peran Budaya Teka Ra Ne'e dalam Mengentaskan Kemiskinan di Bima, NTB - Mega Oktaviany; Nadhirah Nordin; Rahimah Embong (Al-Azhar Journal of Islamic Economics, 2023)
Poverty is a very complex problem for every nation and must immediately get the right solution. Indonesia is a developing country and has a large population, of course it cannot avoid this problem. This is proven by the number of poor people who are increasing every year, even the majority live in rural areas which are difficult to access. Bima is an area located on the island of Sumbawa, West Nusa Tenggara, which is far from urban areas. According to Presidential Decree No. 131 of 2015-2019, when viewed from the data, Bima is an underdeveloped area in terms of human resources and monthly wages that fall into the poor category, as well as infrastructure and others. Even though Bima has very rich cultural and natural resources, as well as human resources that are full of creativity. Therefore this study wants to identify the role of the culture of taka ra ne'e in alleviating poverty in Bima. This study uses a qualitative descriptive methodology with a social phenomenological approach. Subsequent data collection was through observation and unstructured open interviews, then the data was processed with thematic analysis to draw conclusions. Finally, for the validity of the data, the researcher sent back the data according to the research to the informant for a correct data. The results of the study show that the culture of taka ra ne'e is a temporary practice of giving (alms) to the economic life of the Bima community. The culture continues to grow and develop which can be classified into two forms: first from a normative approach and second from socio phenomenology. In addition to cultural practices in Bima using the analysis framework of the charity strategy, this study reveals the intervention of the giving movement in increasing welfare and alleviating poverty in the Bima community through the culture of taka ra ne'e